2021
DOI: 10.1177/03635465211049234
|View full text |Cite
|
Sign up to set email alerts
|

Graft Survivorship After Anterior Cruciate Ligament Reconstruction Based on Tibial Slope

Abstract: Background: Increased tibial slope (TS) is believed to be a risk factor for anterior cruciate ligament (ACL) tears. Increased TS may also promote graft insufficiency after ACL reconstruction. Purpose: To delineate the relationship between TS and single as well as multiple graft insufficiencies after ACL reconstruction. Study Design: Cohort study; Level of evidence 3. Methods: We retrospectively identified 519 patients who had sustained ACL graft insufficiency after primary or revision ACL reconstruction (1 gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 33 publications
2
35
2
Order By: Relevance
“…A high success rate of ACL revision in association with tibial opening osteotomy is reported in the literature, in particular if a concomitant reduction of the slope is performed [ 24 , 25 ]. An increased tibial slope (> 12°) is regarded as a risk factor for not only a first ACL injury but also early failure after ACL reconstruction, due to the excessive tension on the graft [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high success rate of ACL revision in association with tibial opening osteotomy is reported in the literature, in particular if a concomitant reduction of the slope is performed [ 24 , 25 ]. An increased tibial slope (> 12°) is regarded as a risk factor for not only a first ACL injury but also early failure after ACL reconstruction, due to the excessive tension on the graft [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have identified some risk factors for revACLr, such as male sex, young age, and elevated body mass index as well as an early return to sport and pivoting sport after the reconstruction. However, traumatic re-injury is only the tip of the iceberg; there are also many technical factors, such as tunnel malpositioning, inadequate graft fixation, graft choice for primary reconstruction, insufficient anterolateral structures, and an elevated/excessive posterior tibial slope [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… 13 Among several parameters, a large posterior tibial slope has been proven to be one of the strongest risk factors for ACL injuries, as well as graft tear and insufficiency after ACL reconstruction due to increased strain in the ACL and increased anterior tibial translation in ACL-deficient knees. 1 , 2 Therefore, in cases with ACL deficiency involving a large posterior tibial slope, especially in revision cases, anterior closing-wedge osteotomy has been performed as a slope-reducing osteotomy concomitant with ACL reconstruction, and satisfactory clinical outcomes with restored knee stability and graft-failure prevention have been reported. 3 , 4 , 5 However, in such chronic ACL deficiency cases, MM injuries as well as medial compartment OA often are also present, and simultaneous varus and slope correction would be required.…”
Section: Discussionmentioning
confidence: 99%
“…A large posterior tibial slope has been proven to be a risk factor for anterior cruciate ligament (ACL) injuries 1 as well as graft tear and insufficiency after ACL reconstruction. 2 Therefore, in cases of ACL deficiency involving a large posterior tibial slope, especially revision cases, anterior closing-wedge osteotomy as a slope-reducing osteotomy with concomitant ACL reconstruction is considered. 3 , 4 , 5 However, in such chronic ACL deficiency cases, medial meniscus (MM) injuries and medial compartment osteoarthritis (OA) often also are present, and simultaneous varus and slope correction would be required.…”
mentioning
confidence: 99%
“…8,11,13,28 Patients with >12° of PTS, measured according to the proximal anatomic axis, are at high risk for further ACL injuries. 2,7,22,29…”
mentioning
confidence: 99%